(3TQM UOQ TQM GdQSGdI GdTeSjIs - (3HQgGf GdOjf ceGd GdOjf Hf MejOs; (3GdbWH GdJMJGfj , eMeO (B( (3eMehO (B) (3Hf eMeO GdQGRj, CHh YHO Gddg, bWH GdOjf CHh YHO Gddg GdJMJGfj,J (B766 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg fSJYjf hHYO , ajbhd deG cGf UOQ TQM GdCaGVd GdeMbb GdQGRi ddQSGdI GdTeSjI eTMhfkG HGdGSJYGQGJ hGdJTHjgGJ EdJeSJ GdCYRI efi Cf CTQM UOQg aTQYJ ajg s
(3BNQgG (B:s
(3bhdg (B: (3Yf GdNWd Ci Yf aSGO GdcdGe hGdEVWQGH Yf WQjb GdSOGO JeJ s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdeJf HGdMeQIs
(3HBNQgG eSCdI ai EYGOI GdfcQI fcQg hEYGOJgG eYQaI hEYGOI GdeYQaI eYQaI Ch fcQg heG jJQJH Ydi Pdc s
(3hgj HNW eNJda Hbde YHO GdQRGb Hf HcQi GdSeGf s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdadSaI hGdefWbs